2021
DOI: 10.1186/s12893-021-01292-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracardic migration of Kirschner wire from the right sternoclavicular joint: a case report

Abstract: Background Migration of wires and pins within the heart is an uncommon complication. Intracardic migration of Kirschner wire can cause several complications. Case presentation A 55-year-old male patient was admitted to the emergency service with dyspnea, stabbing chest pain. The patient’s medical history showed that he had undergone a fixation operation using Kirschner wire and plate for treatment of the right sternoclavicular joint dislocation abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The use of K-wires has largely been abandoned due to potential complications. [26][27][28][29] There is significant variation in hospital policy regarding the use of cardiothoracic backup during open PSCJi procedures. Fournier and colleagues reviewed 125 patients with acute PSCJi dislocations from 6 institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of K-wires has largely been abandoned due to potential complications. [26][27][28][29] There is significant variation in hospital policy regarding the use of cardiothoracic backup during open PSCJi procedures. Fournier and colleagues reviewed 125 patients with acute PSCJi dislocations from 6 institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Khalil et al 6 describe the temporary use of k-wire fixation to allow for vascular repair. The use of K-wires has largely been abandoned due to potential complications 26–29 …”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the bending wire also experienced migration. This safely assumes that bending the wire solely does not completely prevent the migration since there are many contributing factors, such as high-force movement, gravitational force, intrathoracic pressure, and muscle activity (Wang, et al, 2021). Our patient worked as a mechanic, which required him to do heavy work on his shoulder, so we suggested that a lot of muscle activity and shoulder movement may induce wire migration (Pientka, et al, 2016) Considering the harmful potential of K-wire, X-ray evaluation is also necessary to assess bone healing based on the patient's age and pattern of the injury, which usually takes around 4-6 weeks after surgery unless non-union occurs (Sananta, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…В научной литературе имеются описания случаев миграции спиц Киршнера после операций на опорно-двигательном аппарате с развитием осложнений со стороны внутренних органов [1,2,3].…”
unclassified